MAP2 – A Candidate Gene for Epilepsy, Developmental Delay and Behavioral Abnormalities in a Patient With Microdeletion 2q34 - Westphal, Dominik S.; Andres, Stephanie; Makowski, Christine; Meitinger, Thomas; Hoefele, Julia (Frontiers in Genetics, 2018)
Introduction: Microdeletions in the chromosomal region 2q34 and its neighboring regions lead to a phenotypic spectrum including autism, intellectual disability, and epilepsy. Up to now, only few affected patients have been reported. Therefore, the genetic pathogenesis is not completely understood. One of the most discussed candidate genes in this context is MAP2, a gene responsible for microtubule polymerization and neurite outgrowth. Materials and Methods: We present a 4.5-year-old male patient with epilepsy, mild developmental delay, and behavioral abnormalities. SNP-Array analysis was performed to search for pathogenic copy number variations. Results: SNP-Array analysis revealed a 1.5 Mb de novo microdeletion on the long arm of chromosome 2 (2q34). The identified microdeletion included the candidate genes UNC80, LANCL1, and most importantly MAP2. Discussion: The reported microdeletion identified in this patient is the smallest one described in the literature so far spanning MAP2 next to UNC80 and LANCL1. In this context MAP2 is the most important candidate gene concerning neuronal development and its function should be further examined.